2008
DOI: 10.1007/s10995-008-0361-1
|View full text |Cite
|
Sign up to set email alerts
|

Does the Use of Nicotine Replacement Therapy During Pregnancy Affect Pregnancy Outcomes?

Abstract: Risks of low birthweight and preterm birth were highest for women prescribed or recommended NRT. These findings may be related to frequency of maternal smoking. While heavier smokers may be more likely to be recommended NRT, they also may have the most difficulty with cessation. Greater efforts should be made to ensure that these women do successfully cease smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 16 publications
3
52
0
Order By: Relevance
“…Notably, the use of more than one type of NRT during pregnancy was associated with a small, but not statistically significant, reduction in birthweight (10.7 grams per week). Using the Pregnancy Risk Assessment Monitoring System (PRAMS), investigators in the United States noted that among 5716 women who self-reported smoking during pregnancy, women who had been prescribed NRT had about twice the risk of low birth weight (odds ratio of 1.95) and preterm birth (odds ratio of 2.04) compared with non-smokers [38]. These results are confounded by the high likelihood that women prescribed NRT were heavier smokers during pregnancy.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Notably, the use of more than one type of NRT during pregnancy was associated with a small, but not statistically significant, reduction in birthweight (10.7 grams per week). Using the Pregnancy Risk Assessment Monitoring System (PRAMS), investigators in the United States noted that among 5716 women who self-reported smoking during pregnancy, women who had been prescribed NRT had about twice the risk of low birth weight (odds ratio of 1.95) and preterm birth (odds ratio of 2.04) compared with non-smokers [38]. These results are confounded by the high likelihood that women prescribed NRT were heavier smokers during pregnancy.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Asian/Pacific Islander smokers were the least likely among all of the minority groups to visit a physician (Tong et al, 2011) and receive advice to quit smoking (Chen & Hawks, 1995; Tong et al, 2011). African American, Hispanic, and Asian/Pacific Islander smokers were less likely to use NRT, compared to White counterparts (Trinidad et al, 2011), and the same applies to pregnant smokers of these minority groups (Gaither et al, 2009). African American smokers were the least likely to have a complete home smoking ban, while Hispanic and Asian/Pacific Islander smokers were the most likely to have a complete home smoking ban (Trinidad et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Smoking in pregnancy is related to several adverse outcomes for both mothers and their children 1,2. In the UK, 26% of mothers smoke directly before or during their pregnancy, and 12% continue to smoke throughout 3.…”
Section: Introductionmentioning
confidence: 99%
“…It was initially contraindicated during pregnancy because of a lack of evidence for its safety 8. To date there is no conclusive evidence on its effectiveness during pregnancy,9 and studies of NRT safety during pregnancy are inconclusive 2,1012. Nevertheless, expert consensus is that NRT is likely to be less harmful than smoking during pregnancy and, with various caveats, NRT has been recommended by international guidelines when smoking cessation without NRT is unsuccessful 13–16…”
Section: Introductionmentioning
confidence: 99%